DOI: 10.11606/d.17.2016.tde-05012016-112357
|View full text |Cite
|
Sign up to set email alerts
|

Relação da concentração de metais pesados em amostras de água das bacias dos rios Pardo, Mogi-Guaçu, Sapucaí/Mirim e do aquífero Guarani com a etiopatogênese dos pênfigos

Abstract: Gostaria de agradecer primeiramente a Deus, por sempre ter me guiado, nunca me desamparado e por ter colocado no meu caminho as pessoas maravilhosas, as quais tive o prazer de conhecer e trabalhar nesse período enriquecedor da minha vida. Agradeço à minha orientadora, Dra. Ana, pela confiança que depositou em mim ao me confiar esse trabalho. Sou muito grato pela paciência que teve comigo, pelos valiosos ensinamentos, pela parceria durante esses anos de mestrado e por ser uma pessoa com um astral excepcional. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Agricultural additives, such as fertilizers, pesticides, 42-44 metals, including zinc (Zn), copper (Cu), 45,46 mercury (Hg), 47,48 and lead (Pb) [49][50][51] are considered sources of exogenous agents that may affect the immune system, the onset of pemphigus, and the environment. Studies have shown that PV patients had three-times greater exposure to pesticides than healthy subjects, and the exposure to metals 52 and pesticide vapors may also be associated with worsening of PV. 43,53,54 A study by Alves et al 55 found high Zn values and significant differences between the waters analyzed in the Pardo River (in Ribeirão Preto upstream and downstream), indicating that the use of fertilizers and other agricultural practices (e.g., burning of sugar cane) exert a significant influence on water quality in this city.…”
Section: Discussionmentioning
confidence: 99%
“…Agricultural additives, such as fertilizers, pesticides, 42-44 metals, including zinc (Zn), copper (Cu), 45,46 mercury (Hg), 47,48 and lead (Pb) [49][50][51] are considered sources of exogenous agents that may affect the immune system, the onset of pemphigus, and the environment. Studies have shown that PV patients had three-times greater exposure to pesticides than healthy subjects, and the exposure to metals 52 and pesticide vapors may also be associated with worsening of PV. 43,53,54 A study by Alves et al 55 found high Zn values and significant differences between the waters analyzed in the Pardo River (in Ribeirão Preto upstream and downstream), indicating that the use of fertilizers and other agricultural practices (e.g., burning of sugar cane) exert a significant influence on water quality in this city.…”
Section: Discussionmentioning
confidence: 99%